Cohesins and condensins orchestrate the 4D dynamics of yeast chromosomes during the cell cycle - Lazar‐Stefanita, Luciana; Scolari, Vittore F; Mercy, Guillaume; Muller, Héloise; Guérin, Thomas M; Thierry, Agnès; Mozziconacci, Julien; Koszul, Romain (The EMBO journal, 2017)
Duplication and segregation of chromosomes involves dynamic reorganization of their internal structure by conserved architectural proteins, including the structural maintenance of chromosomes (SMC) complexes cohesin and condensin. Despite active investigation of the roles of these factors, a genome‐wide view of dynamic chromosome architecture at both small and large scale during cell division is still missing. Here, we report the first comprehensive 4D analysis of the higher‐order organization of the Saccharomyces cerevisiae genome throughout the cell cycle and investigate the roles of SMC complexes in controlling structural transitions. During replication, cohesion establishment promotes numerous long‐range intra‐chromosomal contacts and correlates with the individualization of chromosomes, which culminates at metaphase. In anaphase, mitotic chromosomes are abruptly reorganized depending on mechanical forces exerted by the mitotic spindle. Formation of a condensin‐dependent loop bridging the centromere cluster with the rDNA loci suggests that condensin‐mediated forces may also directly facilitate segregation. This work therefore comprehensively recapitulates cell cycle‐dependent chromosome dynamics in a unicellular eukaryote, but also unveils new features of chromosome structural reorganization during highly conserved stages of cell division. Synopsis Hi‐C analysis at 15 distinct stages provides a comprehensive map of chromosome dynamics throughout the budding yeast cell cycle. This illustrates how SMC complexes control chromosome looping and suggests that condensin contributes to chromosome segregation during anaphase. Genome‐wide Hi‐C contact maps provide a comprehensive overview of genome reorganization throughout the cell cycle. Three different chromosome folding states, basic (G1), condensed (metaphase) and extended (anaphase), alternate during the cycle. Altered contacts upon microtubule destabilization imply microtubule‐induced stretching in anaphase. Formation of a condensin‐dependent intra‐chromosomal loop during anaphase bridges rDNA with the centromere, possibly through a loop extrusion mechanism. Graphical Abstract Hi‐C analysis at 15 distinct synchronization stages provides a comprehensive map of chromosome dynamics throughout the budding yeast cell cycle, and illustrates how SMC complexes control chromosome looping.